Analisis Efektivitas dan Efisiensi Anggaran Belanja Daerah BPKAD Kabupaten Bojonegoro 2018-2022 - Rahmawati, Farida; Susanto, Ayogia Ayonono (LPPM Universitas BSI, 2023)
The regional expenditure budget is used as a reference for measuring effectiveness and efficiency in assessing regional government performance. This study aims to be able to analyze the level of effectiveness and efficiency in the regional budget at BPKAD Bojonegoro Regency in 2018-2022. The data used in this study uses data from the Budget Realization Report for 2018-2022 obtained at the BPKAD of Bojonegoro Regency. The method that will be used for this research is to use a quantitative descriptive method. The results of research at BPKAD Bojonegoro Regency in 2018-2022 show the level of effectiveness in 2018-2019 is in the ineffective category. In 2020 it has increased to be quite effective. In 2021 it will decrease to a less effective category. In 2022 it will increase to the effective category. Meanwhile, the level of efficiency in 2018-2020 is categorized as efficient. In 2021-2022 it has a very efficient category.Keyword: Effectiveness, Efficiency, Regional budget